Cecilia Bartoli : the passion of song - Chernin, Kim. 4 0 16; 5 (New York : HarperCollins Publishers, 1997)
An examination of five concerts featuring mezzo-soprano Cecilia Bartoli, along with a 1993 interview. Includes a performance guide and discography
I.A Feather on the Breath of God: The First Three Concerts, 1991-1993 -- II. A Conversation: 1993 -- III. The Barefoot Diva: The Fourth and fifth Concerts, 1994-1995 -- IV. The Master Class: Mother and Daughter in Braunschweig, 1996 -- Performance Guide: 1985-1996 / Renate Stendhal
Discography: pages 211-222;Includes index
Keywords: 2 -- 0; 6; Biography.;Biography.;Biography. -- d; 20; 2